Procedural content generation for C++ game development : get to know techniques and approaches to procedurally generate game content in C++ using Simple and Fast Multimedia Library /: get to know techniques and approaches to procedurally generate game content in C++ using Simple and Fast Multimedia Library. ([2016]) - Green, Dale
No abstract available